Intrinsic impacts of the expression of PD-L1 on postoperative recurrence in EGFR-mutated lung adenocarcinoma - Ito, Atsushi; Kano, Shu; Tarukawa, Tomohito; Suzuki, Yuta; Sakaguchi, Tadashi; Ito, Kentaro; Nishii, Yoichi; Taguchi, Osamu; Yasui, Hiroki; Takao, Motoshi; Hataji, Osamu (Frontiers in Oncology, 2024)
Objectives: This study aimed to assess the intrinsic impacts of the expression of PD-L1 on postoperative recurrence and the prognosis in patients with epidermal growth factor receptor (EGFR)-mutated lung adenocarcinomas. Patients and Methods: Data from 221 surgically resected pathological stage IA–IIIA lung adenocarcinomas, collected between 2017 and 2019, were analyzed. This included measurements of EGFR mutations and the PD-L1 expression. Recurrence-free survival (RFS) and overall survival (OS) were estimated using a Kaplan-Meier analysis and log-rank test. The independent risk factors for RFS were assessed using univariate and multivariate analyses. Results: Among the patients, 140 were PD-L1-negative (<1%), while 81 were PD-L1-positive (≥1%). PD-L1 positivity was significantly associated with male sex (p=0.038), smoking habit (p=0.005), ND2 lymph node dissection (p=0.013), higher malignant subtype (p=0.003), higher histological grade (p=0.001), and advanced pathological stage (p=0.004). Conversely, EGFR mutations were more common in the PD-L1-negative group than in the PD-L1-positive group (p=0.006). Patients were categorized into four groups based on their EGFR mutation status and PD-L1 expression status: PD-L1-positive (≥1%) with or without EGFR mutations (EGFR(+)/PD-L1≥1% or EGFR(-)/PD-L1≥1%), and PD-L1-negative (<1%) with or without EGFR mutations (EGFR(+)/PD-L1<1% or EGFR(-)/PD-L1<1%). Among these groups, EGFR(+)/PD-L1≥1% cases exhibited the worst 5-year RFS (log-rank, p=0.010), while there was no significant difference in 5-year OS (log-rank, p=0.122). Furthermore, a multivariate analysis revealed that PD-L1 positivity was an independent significant factor for RFS in EGFR-mutated lung adenocarcinoma (p=0.013). Conclusion: PD-L1 positivity emerged as an independent risk factor for RFS in patients with EGFR-mutant resected lung adenocarcinoma. These findings may provide valuable insights into the prognostic impact of PD-L1 expression and guide the implementation of postoperative adjuvant therapy in this patient population.